The impact of the global business cycle on small open economies: A FAVAR approach for Canada - Garima Vasishtha; Philipp Maier (Bank of Canada, 2011)
Building on the growing evidence on the importance of large data sets for empirical macroeconomic modeling, we use a factor-augmented VAR (FAVAR) model with more than 260 series for 20 OECD countries to analyze how global developments affect the Canadian economy. We focus on several sources of shocks, including commodity prices, foreign economic activity, and foreign interest rates. We evaluate the impact of each shock on key Canadian macroeconomic variables to provide a comprehensive picture of the effect of international shocks on the Canadian economy. Our findings indicate that Canada is primarily exposed to shocks to foreign activity and to commodity prices. In contrast, the impact of shocks to global interest rates or global inflation is substantially lower. Our findings also expose the different channels through which higher commodity prices impact the Canadian economy: Canada benefits from higher commodity prices through a positive terms of trade shock, but at the same time, higher commodity prices tend to lower global economic activity, hurting demand for Canadian exports.
Keywords: C32; F41; 330; International topics; Econometric and statistical methods; Business fluctuations and cycles; Globalisierung; Internationale Wirtschaftsbeziehungen; Volkswirtschaft; Konjunktur; VAR-Modell; OECD-Staaten; Kanada